Variasi Suhu dan Lama Pengeringan Terhadap Mutu Masakan Sepat Instan - Fadila Hidayatun Oktaviani; Ihlana Nairfana (Jurnal Teknologi dan Mutu Pangan, 2023)
Sepat is a typical Sumbawa dish made from fresh fish that is grilled and mixed with various kinds of spices and complementary ingredients. Because this dish is served fresh, it can only be found on the island of Sumbawa. Sepat has the potential to beprocessed into instant food to increase its marketability. The purpose of this study was to determine the effect of temperature and drying time using a food dehydrator on the organoleptic quality, water content and total microbes of instant sepat. The study was designed using a factorial completely randomized design, namely drying temperature (P) and drying time (W). Nine combinations of drying temperature and time have been studied. Each treatment was repeated 3 times to obtain 27 experimental units. Data wasthenanalyzedusing ANOVA at 5% significant level. Eachdifferent data was further tested using the Duncan Multiple Range Testat a 5% level. The results showed that the temperature and drying time affected the organoleptic quality (aroma, texture and taste), moisture content and total microbe of instant sepat. The drying temperature is 60 ℃ for 16 hours (P2W2) that resulted sepat with a typical sour taste, a texture thatis not too dry, a water content of 9.37% and a total of 4.0 x 104 colonies/g microbes.